Signs and symptoms of anxiety and depression in students of nursing: literature review - Oliveira, Naiane Pinheiro de (2022)
This study aimed to carry out a literature review on the signs and symptoms of anxiety and depression in nursing students. This is a descriptive study with a quantitative approach, of the literature review type. The research was carried out in the databases Base Brazilian Journal of Development (BJD), Revista Eletrônica Acervo Saúde (REAS), Revista Brasileira de Educação Médica (RBEM), Revista Latinoamericana Enfermagem (RLAE), Scientific Electronic Library Online (SciELO). The descriptors performance anxiety, depression and nursing student, found on the Descriptors in Health Sciences (DeCS) platform, were used. Studies that addressed the proposed theme, free full text, Portuguese language, were included. A total of 2,761 studies were found, and after applying the inclusion and exclusion criteria, only 07 articles made up the final sample of the review. Results found on the prevalence and factors associated with anxiety and depression, revealing levels of anxiety of 76.9% mild, 15.4% moderate and 7.7% severe in the Nursing course. In academics, high rate of self-accusation 51.72%, 67.28% of irritability, 58.62% of loss of appetite, 38.69% of crying spells, 38.8% of social withdrawal, 44.84% of indecision for with life. These numbers are related to the vulnerability that students have to depressive symptoms, arising from excesses of anxiety, preoccupation with grades, high workload and studies, and social withdrawal. Therefore, the results contributed with data to support new studies and tools for the prevention, promotion and recovery of nursing students' mental health.